Metformin-induced hypomagnesaemia in a patient with diabetes: a case report - Lara Abu-Qutaish; Rakshit Kumar (Clinical Medicine, 2025)
Introduction: Hypomagnesaemia is frequently encountered among diabetic patients; however, the potential relationship between prolonged metformin use and hypomagnesaemia remains under-recognised in clinical practice. In this report, we present a case of severe hypomagnesaemia in a 76-year-old patient with longstanding diabetes, which highlights the importance of considering metformin as a potential contributing factor in hypomagnesaemia. Case presentation: A 76-year-old patient was referred to our same-day medical assessment (SDMA) unit because of persistent, severe hypomagnesaemia of 0.3 mmol/L initially identified in primary care. Her past medical history included longstanding diabetes, heart failure (HF) with preserved ejection fraction, chronic kidney disease (CKD) stage 2, atrial fibrillation (AF), previous ischaemic heart disease (IHD) and polymyalgia rheumatica. Her medications included metformin, insulin, furosemide, bisoprolol, atorvastatin, ramipril, rivaroxaban, isosorbide mononitrate, prednisolone, ferrous sulfate and calcium supplements.She was prescribed a course of oral magnesium replacement by her GP. However, her serum magnesium levels remained low at 0.3 mmol/L. Thus, she was sent for intravenous replacement and medical assessment. Intravenous replacement, supplemented by ongoing oral replacement, raised her magnesium level to 1.1 mmol/L. A medical review identified chronic metformin use as the most likely cause for her severe hypomagnesaemia. Thus, her metformin was stopped, and her insulin dose was increased to make up for stopping the metformin. Follow-up blood tests revealed a stable serum magnesium level at 0.7 mmol/L without the need for further supplementation. Discussion: Chronic hypomagnesaemia in diabetic patients has been associated with multiple negative clinical outcomes, such as increased insulin resistance, hypertension and heightened risk of cardiac arrhythmias.1,2 Thus, any medication contributing to reduced serum magnesium levels can have substantial clinical implications for patients with diabetes.Several observational and interventional studies suggest a notable association between metformin and hypomagnesaemia. The Fremantle Diabetes Study identified a clinically significant correlation, with metformin users demonstrating notably lower serum magnesium levels compared with those managed by diet alone.2 Similarly, a large cross-sectional study observed an inverse correlation between serum magnesium levels and metformin use, with longer durations of therapy and multiple antidiabetic medications compounding this effect.3Additionally, an earlier interventional trial comparing metformin with sulfonylureas (glipizide specifically) found that, despite comparable glucose control in both groups, those on metformin remained hypomagnesemic, whereas those on glipizide showed a significant rise in serum magnesium.4Several pathophysiological mechanisms have been proposed to explain metformin-associated magnesium depletion. These include impaired gastrointestinal magnesium absorption, likely mediated by downregulated transient receptor potential melastatin 6 (TRPM6) channels, gastrointestinal magnesium losses because of chronic metformin-related diarrhoea, and potentially reduced renal reabsorption of magnesium.5,6 Conclusion: This case highlights the importance of considering metformin-induced hypomagnesaemia as a differential diagnosis in diabetic patients presenting with persistent or refractory hypomagnesaemia. Given the widespread prescription of metformin, especially among older diabetic patients with CKD or polypharmacy, routine monitoring of serum magnesium is advisable. In cases of severe or refractory hypomagnesaemia, timely identification and intervention, including withdrawal of metformin if needed, as well as magnesium supplementation, are crucial to prevent severe hypomagnesaemia-related complications. Further studies are also needed to fully clarify this relationship between magnesium levels and metformin use.